Private equity Buyout transactions – General Partner’s value generation and multiple expansion - Kauppinen, Emmi (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2017)
When it comes to investment returns in private equity, the difference between the entry and exit pricing is a critical factor for the successful profitable investment. Between the entry and exit phases private equity firms are creating value in the target companies by improving operational functions and creating profitable growth. Usually the value creation within the holding period can be categorized in two categories; the financial engineering and operational developments. These include valuation multiple expansion, which is determined as the change in the valuation multiple from the entry to exit. While some of the operational levers in the deal’s value generation can be captured easily, the valuation multiple expansion is a complex lever, which is affected by various visions and facts. Considering the significance of the value generation in successful private equity deals, we should understand the concept comprehensively. However, the knowledge is not in that level yet. There exists a general need for such understanding of value generation and, especially, the multiple expansion. This thesis contributes to the academic literature of private equity investments by analyzing the multiple expansion and levers behind. The thesis introduces the theoretical concept of value generation in the deal-level and analyzes the impact of operational factors of multiple expansion in the empirical part. Deal’s revenue growth and EBITDA margin are operational levers of multiple expansion and these are the main factors in the hypotheses. In addition to the regression analysis regarding the impact of revenue growth and EBITDA margin to multiple expansion the thesis introduces other fascinating factors of the empirical sample of 98 buyout deals. The outcome of the regression analysis contributes to the academic literature with the confirmation of a negative impact of EBITDA margin improvements on multiple expansion, however the impact of revenue growth remains to be determined by other studies.

Pääomasijoittaminen on tullut yhä suositummaksi viimeisen kahdenkymmenen vuoden aikana. Akateeminen tutkimus pääomasijoittamisesta on pääasiassa keskittynyt tutkimaan sijoittajille realisoituvia tuottoja ja näiden suuruutta suhteessa esimerkiksi osakemarkkinoihin. Viime vuosina huomio on kuitenkin kääntynyt enemmän ja enemmän itse pääomasijoitusyhtiöissä tapahtuvaan arvonluontiin ja sen vaikutukset ovat nousseet yhä enemmän korostettuun asemaan kun tarkastellaan pääomasijoittamisen yrityskohtaisia tuottoja. Arvonluonti pääomasijoitusyrityksissä voidaan jakaa operationaalisiin ja rahoituksellisiin tekijöihin ja pelkistetysti tätä toteutetaan neljän faktorin kautta. Liikevaihdon, EBITDA- %:in, Arvostuskertoimen (”valuaatiokerroin”) ja velan muutokset nähdään merkittävimmiksi yritystason arvonluonnin välineiksi joita pääomasijoitusammattilaisten tulee hyödyntää investointiaikana. Näistä parametreista kolme määritellään suhteellisen selkeästi yrityksen tilinpäätöksistä, mutta yrityksen valuaatiokerroin ei ole yhtä suoraviivainen määriteltäväksi. Akateeminen tutkimus onkin kääntänyt katseensa valuaatiokertoimen muutoksiin pääomasijoittajan investointiperiodin aikana sekä tämän vaikutuksiin sijoittajille realisoituvan tuottoon. Tässä tutkielmassa tutkin yhtiön valuaatiokertoimen muutokseen vaikuttavia tekijöitä pääomasijoittajan omistuksen aikana testaamalla liikevaihdon ja EBITDA- %:in muutoksien vaikutuksia yhtiön arvostuskertoimiin empiirisellä aineistolla, joka koostuu 98:sta Buyout – pääomasijoitusyhtiöstä. Tutkielma esittelee teoreettiset lähtökohdat pääomasijoittajan arvonluonnille yhtiössä, regressioanalyysin sekä kattavan analyysin aineiston yhtiöitä koskevista muista mielenkiintoisista piirteistä. Tutkielma löytää tilastollisesti merkittäviä tuloksia hypoteesilleen EBITDA- %:in vaikutuksesta arvostuskertoimien kasvuun, mutta ei pysty näyttämään hypoteesille liikevaihdosta puoltavia eikä kieltäviäkään tuloksia